If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1 + 6r) + r = 14 (1 * -3 + 6r * -3) + r = 14 (-3 + -18r) + r = 14 Combine like terms: -18r + r = -17r -3 + -17r = 14 Solving -3 + -17r = 14 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -17r = 14 + 3 Combine like terms: -3 + 3 = 0 0 + -17r = 14 + 3 -17r = 14 + 3 Combine like terms: 14 + 3 = 17 -17r = 17 Divide each side by '-17'. r = -1 Simplifying r = -1
| 3r=(14+10r) | | 8+9x-1=7x+35-2x | | -y-8=3y | | x(x+18)=(x+9)2 | | 8y+11=51 | | X+21+4x=-27-4x-33 | | 6x=56-2x | | -109=-5(3m-1)+6 | | 3L+3(L-5)=135 | | 7u^6-32u^5-15u^4= | | 2x+11y=17 | | 27=1s-9 | | 6(6p+6)-6p=6 | | 9(4x-5)=7(x+2)-6 | | 3x+10=6x-10 | | 4(-3x+1)=3(7-2x) | | -2+9=15x-5-14x | | -x+5y=20 | | 7m=(m+4)3 | | a+1.25=2a-1 | | 56-24q=17q | | 450.75=3.25w-250.50 | | 6x+9-5x=13 | | 6v^7-22v^6+20v^5= | | 26-8k=3(8k-2) | | 3(4x-2)-(5x+6)=44 | | (2n+5)-3(3n+1)=-21 | | (-4p-6)=2p | | 7(2-x)-3(x+1)+3(9-(4-2x))=18 | | 4(3-6v)-7v=12-4v | | 6+19z-1=7z+33-2z | | 9x-(7x-7)=16 |